2022
DOI: 10.1016/j.ajic.2021.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Contact tracing as a measure to combat COVID-19 and other infectious diseases

Abstract: Background: Most of the mathematical modeling studies on COVID-19 transmission are based on continuous deterministic models that do not consider the characteristics of social network. Methods: The effect of contact tracing on mitigating COVID-19, and other infectious diseases in general, is studied in a small-world network. This network has its advantages over the commonly used continuous deterministic mathematical models in that the characteristics of social networks can be properly incorporated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…proactive and targeted control measures to counter this newer variant having the substantial advantage of speedy transmission, and also the Delta variant needs to be given the top priority at the global level amid the ongoing pandemic. 11,26,33,[39][40][41][42][43][44][45][46][47][48][49]…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…proactive and targeted control measures to counter this newer variant having the substantial advantage of speedy transmission, and also the Delta variant needs to be given the top priority at the global level amid the ongoing pandemic. 11,26,33,[39][40][41][42][43][44][45][46][47][48][49]…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In conclusion, rapid detection, genomic surveillance, and evolutionary dynamics studies should be carried out at an enhanced pace along with contact tracing of variants, gaining more knowledge on this variant (Omicron) along with updating the current COVID‐19 vaccines, developing second‐generation vaccines, ramping up of vaccination drives with incorporating booster shots, finding out treatable options from a drug developer's perspective as well as strengthening and strict implementation of adequate mitigation and proactive and targeted control measures to counter this newer variant having the substantial advantage of speedy transmission, and also the Delta variant needs to be given the top priority at the global level amid the ongoing pandemic. 11 , 26 , 33 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 …”
mentioning
confidence: 99%
“…Contact tracing is a crucial public health strategy used to control the spread of infectious diseases like COVID-19 [72][73][74][75]. When someone tests positive for the virus, public health officials work to identify and notify individuals who have been in close contact with the infected person during the time they may have been contagious.…”
Section: Contact Tracingmentioning
confidence: 99%
“…One of the most essential strategies to help mitigate the spread of infectious diseases is contact tracing (CT) [ 1 ], which was the driving strategy leading to the global eradication of smallpox and is still used to control the transmission of infectious diseases, such as the regularly resurging Ebola [ 2 ]. Studies conducted during the COVID-19 pandemic have also shown CT to be effective in preventing a substantial number of new infections [ 3 , 4 ]. CT traditionally consists of 3 phases: identification (first phase) and notification (second phase) of the contacts of individuals with COVID-19 and monitoring the health (third phase) of individuals with COVID-19 and their contacts.…”
Section: Introductionmentioning
confidence: 99%